1974
DOI: 10.1083/jcb.61.3.789
|View full text |Cite
|
Sign up to set email alerts
|

Selective Release of Content From Microsomal Vesicles Without Membrane Disassembly

Abstract: Rough and smooth microsomes were shown to have similar sets of polypeptide chains except for the proteins of ribosomes bound to the rough endoplasmic reticulum (ER) . More than 50 species of polypeptides were detected by acrylamide gel electrophoresis, ranging in molecular weight from 10,000 to approximately 200,000 daltons . The content of rough and smooth microsomes was separated from the membrane vesicles using sublytic concentrations of detergents and differential centrifugation . A specific subset of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 61 publications
(62 reference statements)
3
65
0
Order By: Relevance
“…Although peripheral membrane proteins are removed from membranes by chelation of divalent cations or incubation in media of high ionic strength (28,29), the newly synthesized ATPase remained associated with the vesicles after ribosomes were detached by treatment with EDTA in a medium containing 0.5 M KC1. Furthermore, a major fraction of the in vitro synthesized ATPase was not released from microsomes by treatments that open microsomal vesicles and release their lumen contents (24,25). Only at deoxycholate concentrations that dissolved the membranes was a substantial fraction of the labeled ATPase released.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although peripheral membrane proteins are removed from membranes by chelation of divalent cations or incubation in media of high ionic strength (28,29), the newly synthesized ATPase remained associated with the vesicles after ribosomes were detached by treatment with EDTA in a medium containing 0.5 M KC1. Furthermore, a major fraction of the in vitro synthesized ATPase was not released from microsomes by treatments that open microsomal vesicles and release their lumen contents (24,25). Only at deoxycholate concentrations that dissolved the membranes was a substantial fraction of the labeled ATPase released.…”
Section: Discussionmentioning
confidence: 90%
“…Subfractionation by differential centrifugation (1 hr at 45,000 X g) showed that the lower deoxycholate concentration used (0.1 mg/mg of microsomal protein in 0.3 ml containing 2.11 X 105 cpm) released 40% of the total microsomal-radioactivity, but labeled ATPase represented only 0.29% of the total radioactive protein in the released fraction. The bulk of the newly synthesized ATPase (0.98% of the radioactivity) was only released at a higher deoxycholate concentration (0.5 mg/mg of protein in 0.3 ml), which is known to cause extensive membrane dissolution (24,25). The major labeled product present in immunoprecipitates obtained from in vitro translation mixtures containing bound polysomes or rough microsomes had an electrophoretic mobility similar to that of the mature ATPase (Fig.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, studies performed in three granular systems other than the rabbit parotid--the guinea pig exocrine pancreas, the rat liver, and the bovine adrenal medulla--have given indication that removal of polypeptides known not to be membrane proteins to limiting levels of detectability has not been attained (47,37,26,68,70). In these studies the contaminating proteins are again secretory proteins identified by enzymatic activity, by comparative gel electrophoresis with soluble extracts of the fractions under investigation, or by a characteristic high rate of incorporation of radioactively tagged amino acid during pulse labeling.…”
Section: Castle Et Al Secretion Granules O F the Rabbit Parotid Glanmentioning
confidence: 99%
“…In the case of rough microsomes isolated from rat liver, treatment with low concentrations of sodium deoxycholate, shown to create discontinuities in the microsomal membranes (35), promotes only partial extraction of short term-labeled (30-rain postpulse) polypeptides identified as protein destined for export from the liver (37). Thus both these studies suggest that adsorption to either the cytoplasmic or cisternal surfaces of membranebounded compartments as a consequence of cell or cellular compartment disruption in nonphysiologic media is both substantial and difficult to overcome by a variety of extractants.…”
Section: Castle Et Al Secretion Granules O F the Rabbit Parotid Glanmentioning
confidence: 99%